Removal of Metal Ions From Aqueous Solutions Using Sawdust Modified with Citric Acid or Tartaric Acid - Yang, Jung-Seok; Park, Young-Tae; Baek, Kitae; Choi, Jaeyoung (TAYLOR & FRANCIS INC, 2010)
This study describes the adsorption of heavy metal ions (Cd(II), Cu(II), Ni(II), Pb(II), and Zn(II)) from aqueous solutions by pine (Pinus densiflora) sawdust modified with citric acid (CA) or tartaric acid (TA). The optimal parameters, contact time, and pH were determined and the adsorption isotherms were obtained. The removal efficiency of the modified sawdust increased as the pH increased. The maximum adsorption capacity of sawdust modified with CA or TA was 14 to 57 times higher than that of unmodified sawdust. These results indicate that either CA or TA can be used to enhance the removal of heavy metals using sawdust.